Effect of glyphosate management, formulations, and rates on agronomic performance of maize with cp4epsps gene - Junior Paiola Albrecht, Alfredo (2023)
Second-generation glyphosate-tolerant maize (Roundup Ready 2, RR2) is characterized by the expression of the cp4epsps gene. Though some studies suggested possible undesirable effects due to glyphosate application in RR2 maize, other reports have demonstrated glyphosate selectivity for RR2 plants, with minor injury symptoms, if any, and without negative effects on chlorophyll indices.